La phrase comme trait de style. L’exemple du roman en vers au xiiie siècle - Vanessa Obry (Perspectives Médiévales)
The verse novels of the early thirteenth century are often analysed as disruptive texts in terms of their relationship to earlier models. Within this framework, the study of the syntax specific to the various authors leads to the distinction of more or less broken styles, which can be linked to the singularity of literary projects or relationships to tradition. This article compares examples from the works of Jean Renart, Raoul de Houdenc and Gerbert de Montreuil in order to re-evaluate the relevance of a syntactic analysis for research on the authors’ style and identify the characteristic trends of a generation. He reflects on the value to be attributed to features of syntactic regularity and irregularity and the phenomena of variations in the rhythm of syntax. The analysis, conducted on a local scale, shows how these rhythmic inflections combine with how the authors deal with inherited motifs, the phenomena of regularity constituting appeals to recognition and memory. The authorial posture implied by the syntactic variations thus seems to reflect a mode of literary communication characteristic of these novels, which are addressed to informed readers.